Fenofases florales en quercus rotundifolia lam. (II Congreso Forestal Español, 1997)
In this work the floral stages are introduced that it is happened in the masculine and feminine flowering of the holm-oak (Quercus rotundifolia Lam.). In each described stages they incorporate data on the floral morphology: state of development that it reach the catkins, the floral group and the tlowers. Also data of the receptive state in the are inserted feminine tlowers and ripening and viability grade of the grain of ponen and ovule. Finally is represented in a graphic each one of the described stage. K.W.: